2019
DOI: 10.1111/bjop.12427
|View full text |Cite
|
Sign up to set email alerts
|

A new conception of visual aesthetic sensitivity

Abstract: Aesthetic sensitivity has been defined as the ability to recognize and appreciate beauty and compositional excellence, and to judge artistic merit according to standards of aesthetic value. The Visual Aesthetic Sensitivity Test (VAST) has often been used to assess this ability, but recent research has revealed it has several psychometric problems. Such problems are not easily remedied, because they reflect flawed assumptions inherent to the concept of aesthetic sensitivity as traditionally understood, and to t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
142
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(164 citation statements)
references
References 111 publications
(225 reference statements)
17
142
2
3
Order By: Relevance
“…Corradi et al () propose that the current conception of aesthetic sensitivity – as the ability to identify aesthetic quality in conformity with external standards (e.g., expert consensus) – needs replacement into a new conception: Aesthetic sensitivity should be redefined as the extent to which certain features of a stimulus are used to form a subjective aesthetic judgment. Although their proposed approach has merits, their (unnecessary) comparison is biased in several ways.…”
Section: Introductionmentioning
confidence: 99%
“…Corradi et al () propose that the current conception of aesthetic sensitivity – as the ability to identify aesthetic quality in conformity with external standards (e.g., expert consensus) – needs replacement into a new conception: Aesthetic sensitivity should be redefined as the extent to which certain features of a stimulus are used to form a subjective aesthetic judgment. Although their proposed approach has merits, their (unnecessary) comparison is biased in several ways.…”
Section: Introductionmentioning
confidence: 99%
“…Others have noted that certain theoretical ideas that combine earlier intuitions about taste, with novel interests in objective factors relating to aesthetic appreciation and artistic ability such as Burt and Eysenck's notion of aesthetic sensitivity, start to take off after 1920 (Che, Sun, Gallardo, & Nadal, 2018;Corradi, Chuquichambi, Barrada, Clemente, & Nadal, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Most frequently, visual aesthetic sensitivity tests operationalize Child's (1964) definition using "controlled alteration" (Meier, 1928, p. 188), a procedure which consists of deteriorating or creating an altered version of an aesthetic stimulus, and in presenting examinees with the altered and original stimuli, with the task of recognizing which is of better aesthetic quality. The construct validity of tests based on it are however controversial (Gear, 1986;Liu, 1990;Corradi et al, 2019), as it was notably argued that absolute aesthetic standards cannot exist, dismissing any operationalization of Child's definition. Nevertheless, the availability of absolute standards is not a necessary condition for the operationalization of Child's definition (Myszkowski et al, 2020): Aesthetic sensitivity tests rely instead on empirical standards, obtained through expert and/or laypeople consensus.…”
Section: Elements Of Validity Of Visual Aesthetic Sensitivity Measuresmentioning
confidence: 99%
“…Another sign of construct validity can be found in the concurrent validity of visual aesthetic sensitivity tests. This point is also quite controversial (Corradi et al, 2019;Myszkowski et al, 2020), but this is mainly because the nomological network of visual aesthetic sensitivity is yet to be clearly defined. Notably, Eysenck introduced confusion by originally discussing the construct as intelligence in the aesthetic domain (1940) to then speculate that the construct should be independent from intelligence (Frois and Eysenck, 1995)-which is contradicted in a recent meta-analysis (Myszkowski et al, 2018), which showed across 23 studies that its correlation with intelligence is significant and around 0.30.…”
Section: Elements Of Validity Of Visual Aesthetic Sensitivity Measuresmentioning
confidence: 99%